Association between Postural Orthostatic Tachycardia Syndrome and Joint Hypermobility. (28th April 2021) - Atuesta-Rodriguez, Alexis Javier; Medina-Velasquez, Yimy F.; Motta, Orfa; Narvaez-Reyes, Maria Isabel; Rondon-Herrera, Federico
Abstract : Joint hypermobility syndrome refers to increased joint flexibility beyond the normal range of motion. This syndrome has a benign form known as Ehlers-Danlos syndrome type 3. This is a disorder in which hypermobility is accompanied by clinical manifestations in the absence of any systemic disease. A clinical finding associated with this condition is postural orthostatic tachycardia syndrome. The following is a rare case of joint hypermobility syndrome and postural orthostatic tachycardia syndrome. The relevance of this case report lies in the impact that this disease had on the patient's quality of life and the limitation in the performance of activities of daily living.